Perancangan Buku Ilustrasi Anak sebagai Media Edukasi untuk Meningkatkan Kesadaran Merawat Gigi dalam Mencegah Karies pada Anak Usia 6-9 Tahun: Designing a Children’s Illustration Book as an Educational Medium to Raise Awareness of Dental Care in Preventing Cavities in Children Aged 6-9 Years - Alfaruqy, Doni; An Nur, Muhammad Hajid; Rohman, Tefur Nur; Prayogi, Candra; Kholida, Putri; Susanti, Susi; Jaelani, Jejen (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Dental caries is one of the major health issues among school-aged children, particularly in the age range of 6-9 years. The lack of awareness about the importance of maintaining dental health from an early age is a contributing factor to the high prevalence of caries in children, which can be addressed through interactive media like illustrated books. This community service project aims to raise awareness about dental care among first-grade students at SD Negeri 2 Harapan Jaya, Sukarame, Bandar Lampung. The methods used include a pre-test, group reading sessions, reading the illustrated book, and a post-test. The pre-test results showed an improvement in students' understanding of dental health after reading the illustrated book, with post-test scores being higher than pre-test scores. This interactive illustrated book provides an engaging and easy-to-understand way of conveying health information, making it a useful tool for dental health education.